1978
DOI: 10.1071/bi9780355
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Enzymes of Glycogen Metabolism in the Reproductive Tract of the Ewe at Mating and during Early Pregnancy

Abstract: The glycogen concentration and the activity of several enzymes of glycogen metabolism have been measured in the mucosal tissues of the oviduct, cervix and vagina, as well as in the endometrium and caruncIes of ewes at days 0, 8, 15, 22, 30 and 44 of pregnancy. Enzyme activities were also determined in uterine and cervical rinsings.Glycogen levels decreased after day 8 in the endometrium, caruncIes, cervix and vagina. Independent glycogen (starch) synthase showed decreased activity in the cervical mucosa follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…2 ). These findings agree with those for animals that do not exhibit obligatory embryonic diapause such as rodents [ 12 ], cats [ 28 ], ferrets [ 29 ], and sheep [ 30 ], illustrating that uterine glycogen reserves are a potential source of energy for uterine and pre-embryonic growth through implantation and early pregnancy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…2 ). These findings agree with those for animals that do not exhibit obligatory embryonic diapause such as rodents [ 12 ], cats [ 28 ], ferrets [ 29 ], and sheep [ 30 ], illustrating that uterine glycogen reserves are a potential source of energy for uterine and pre-embryonic growth through implantation and early pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…Glycogen may also be degraded intra-luminally, as glycogen granules contain anabolic and catabolic enzymes. As evidence, glycogen phosphorylase activity in sheep uterine luminal fluids increased during pre-implantation, peaking near the expected time of implantation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gluconeogenesis does not occur in the uterus (Zimmer & Magnuson, ; Yánez et al, ) and glucose in uterine secretions is derived from the maternal circulation and/or catabolism of uterine glycogen reserves (Demers, Yoshinaga, & Greep, ; Leese et al, ). In sheep and rodents, uterine glycogen concentrations peak during pro‐estrus and estrus, and are mobilized during implantation and pregnancy (Demers et al, ; O'Shea & Murdoch, ). In mink, uterine glandular and luminal epithelial glycogen concentrations were highest during estrus and decreased 99% by the peri‐implantation period (Dean, Hunt, McDougall, & Rose, ).…”
Section: Introductionmentioning
confidence: 99%
“…This was despite a high level of glycogen synthase. The increase in oviducal IX-amylase activity at oestrus did not reach significance, but studies on pregnant ewes have shown a steady decrease after oestrus in IX-amylase activity in the oviduct (O'Shea and Murdoch 1978a). Thus the two catabolic enzymes measured had different patterns during the oestrous cycle with total glycogen phosphorylase showing a rise from day 1 to day 8, whereas IX-amylase showed maximum activity at day O.…”
Section: Discussionmentioning
confidence: 88%